FUNCTIONAL TRAINING FOR CHILDREN - Nascimento de Brito e Silva, Thales; Balbi da Silva, Alessandra (Health and Society, 2023)
With the current situation in society, in which a sedentary lifestyle is part of everyday life, it is necessary to create alternatives to develop and improve the physical qualities of healthy children and adolescents with safe and effective conditioning methods to meet their various needs, goals and capabilities. It is justified by the need to have a clear, precise and defined survey of physical activities that can be applied functionally to children. This prevents physical, mental and social health problems. It aims to identify, from a literature review, which physical activities can be taught to children in functional training. The research is a bibliographical review where 10 articles published between the years 2013 and 2023 were selected. The methodological proposals related to functional training for children must be at the discretion of the teacher in order to adopt the best practice and must encourage them in the search for a healthier lifestyle, combating a sedentary lifestyle and preventing obesity, which is a major cause of physical inactivity in children.